2008
DOI: 10.1118/1.2962702
|View full text |Cite
|
Sign up to set email alerts
|

WE-C-AUD C-05: Analysis of Best Fitting Tomo Treatment Planning Parameters for Prostate, Lung, Breast, Brain, Liver, Head & Neck, Breast, Pelvis and Pancreas Lesions From Our 3 Years Experience Planning for Nearly 1000 Patients

Abstract: Purpose: Best fitting Tomotherapy treatment planning parameters for nine different lesion sites. Method and Materials: Tomotherapy treatment planning and delivery depends on parameters that are not necessarily familiar to a radiotherapy physicist. It is important for planners to familiarize themselves with these parameters and their impact on the time required for delivery: 51 Prostate plans, 268 lungs, 197 Brain, 21Liver, 38 Head & Neck, 46 Breast, 51Pelvis and 59 Pancreas plans for parameters like Pitch, Gan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A review of the literature shows that reported TomoTherapy delivery times for prostate cancer (the disease most frequently mentioned as being treated with RapidArc) are in the range of 4-7 min (3,4). A recent report on treatment delivery parameters for nearly 1,000 patients with nine disease types, treated at a single institution, revealed that average delivery times ranged between 266 and 429 s (5). Further reductions in delivery time by 13%-66% (in other words, reducing the time to less than 3 min in many cases) have been demonstrated using a strategy of decreasing number of gantry rotations and modulation factor, without significantly compromising plan quality (6).…”
mentioning
confidence: 96%
“…A review of the literature shows that reported TomoTherapy delivery times for prostate cancer (the disease most frequently mentioned as being treated with RapidArc) are in the range of 4-7 min (3,4). A recent report on treatment delivery parameters for nearly 1,000 patients with nine disease types, treated at a single institution, revealed that average delivery times ranged between 266 and 429 s (5). Further reductions in delivery time by 13%-66% (in other words, reducing the time to less than 3 min in many cases) have been demonstrated using a strategy of decreasing number of gantry rotations and modulation factor, without significantly compromising plan quality (6).…”
mentioning
confidence: 96%